Activated Carbon Adsorbent From Jengkol Peel For Dye Removal Equilibrium, Kinetic And Thermodynamic Studies - Mohd Ramli, Mohamad Razif (Universiti Sains Malaysia, 2018)
Nowadays, textile industry has been recognized as the most significant source of wastewater pollution mostly related to dyes which directly released into water bodies, resulting in various environmental impacts. These dyes are always released in industrial waste, leading to disposal problem. In the recent years, growing research interest in conversion of agricultural waste into activated carbon (AC) as adsorbent for treating dyes wastewater. The aim of this research is to study the performance of AC derived from jengkol peel (JP) for removal of Methylene Blue (MB) dye by using physical activation which involves carbon dioxide (CO2) gasification and microwave radiation. Optimum conditions for preparation jengkol peel activated carbon (JPAC) were found at 400 W of radiation power and 4 minute activation time which resulted 92.6% MB removal. Optimized JPAC has Bruneaur-Emmet-Teller (BET) surface area, mesopore surface area, pore volume, fixed carbon content of 474.03 m2/g, 332.64 m2/g, 0.389 cm3/g, and 70.45 % respectively. The pore diameter of JPAC was discovered to be mesoporous at 4.28nm. Adsorption equilibrium of MB on JPAC followed Freundlich isotherm. Kinetic studies of adsorption onto JPAC fit by pseudo-second order kinetic models. Thermodynamic study shows the value of ∆Ho was negative which gave an indication that the adsorption was exothermic process.